Comparative anatomy and 3D geometric morphometrics of the El Sidrón atlases (C1). Issue 149 (December 2020) - Palancar, Carlos A.; Torres-Tamayo, Nicole; García-Martínez, Daniel; García-Tabernero, Antonio; Rosas, Antonio; Bastir, Markus
Abstract: The first cervical vertebra (atlas, C1) is an important element of the vertebral column because it connects the cranial base with the cervical column, thus helping to maintain head posture and contributing to neck mobility. However, few atlases are preserved in the fossil record because of the fragility of this vertebra. Consequently, only eight well-preserved atlases from adult Neandertals have been recovered and described. Here, we present nine new atlas remains from the El Sidrón Neandertal site (Asturias, Spain), two of which (SD-1643 and SD-1605/1595) are sufficiently well preserved to allow for a detailed comparative and three-dimensional geometric morphometric analysis. We compared standard linear measurements of SD-1643 and SD-1605/1595 with those of other Neandertal atlases and carried out three-dimensional geometric morphometric analyses to compare size and shape of SD-1643 and SD-1605/1595 with those of 28 Pan ( Pan troglodytes and Pan paniscus ), a broad comparative sample of 55 anatomically modern humans from African and European populations, and other fossil hominins (Neandertals, Homo antecessor, Paranthropus boisei ). The El Sidrón atlas fossils show typical features of the Neandertal atlas morphology, such as caudal projection of the anterior tubercle, gracility of both the posterior tubercle and the tuberosity for the insertion of the transverse ligament, and an anteroposteriorly elongated neural canal. Furthermore, when compared with atlases from the other taxa, Neandertals exhibit species-specific features of atlas morphology including a relatively lower lateral mass height, relatively narrower transverse foramina, and flatter and more horizontally oriented articular facets. Some of these features fit with previous suggestions of shorter overall length of the cervical spine and potential differences in craniocervical posture and mobility. Our results may support a different spinopelvic alignment in this species, as the atlas morphology suggests reduced cervical lordosis.